Integrasi Kurikuler Dalam Meningkatkan Kualitas Pendidikan Agama Islam di Madrasah Aliyah Negeri (MAN) 1 Kuningan - Sopidi, Sopidi; Nugroho, Dimas Aji; Syibromilisi, Syibromilisi (Permata : Jurnal Pendidikan Agama Islam, 2024)
Improving the quality of Islamic education at Madrasah Aliyah requires a holistic approach, one of which is through curricular integration. This research aims to analyze the implementation of synchronization integration in improving the quality of Islamic religious education at Madrasah Aliyah Negeri (MAN) 1 Kuningan. The research method used is a qualitative approach, aiming to explain phenomena such as implementation, policies, curricular integration, evaluation, etc., holistically. Data collection includes observation, interviews, and documentation, with data analysis techniques involving data reduction, presentation, and conclusion drawing. Findings indicate that all elements and activities at MAN 1 Kuningan show integration or interdependence, enhancing effective and efficient learning and producing quality students ready to adapt to society. Additionally, curricular integration at MAN 1 Kuningan focuses not only on knowledge transfer but also on character and ethics development. Results show that students not only understand religious concepts but also apply them in daily life, thus forming a strong foundation for achieving Islamic educational goals of intellectual excellence and moral integrity. Keywords: Integration; Curricular; PAI